The Influence of Human Resource Competency and Budget Preparation Participation on the Quality of Cibinong Hospital Financial Reports Using Information Technology as a Mediating Variable - Sukardiyanto; Titing Widyastuti (Pustaka Digital Indonesia, 2025)
The need for accurate, reliable, and accountable financial reports continues to grow along with the increasing complexity of hospital services. High-quality financial reporting serves as a basis for decision-making. This study aims to analyze the influence of human resource competence and budget preparation participation on the quality of financial reports at Cibinong Regional General Hospital, with information technology utilization as a mediating variable. This research employs a quantitative approach using a questionnaire distributed to 30 respondents, selected through saturated sampling, representing all employees in the finance and budget realization division at Cibinong Regional General Hospital, Bogor Regency. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS to examine both direct and indirect relationships among variables. The results show that human resource competence and budget preparation participation have a positive and significant effect on the utilization of information technology. Human resource competence also has a significant effect on the quality of financial reports. However, budget preparation participation does not significantly affect financial report quality. Furthermore, information technology utilization has a positive and significant influence on financial report quality but does not mediate the relationship between human resource competence and financial report quality. These findings emphasize the importance of improving human resource competence and optimizing the use of information technology to enhance the quality of financial reporting at Cibinong Regional General Hospital.